The conflict of laws in India : inter-territorial and inter-personal conflict - Govindaraj, V. C. (New Delhi : Oxford University Press, 2019)
Conflict of laws, or private international law, is an increasingly important subject of study due to increasing movement & relocation of large number of people from one jurisdiction to another for personal & professional reasons. This text is a detailed & up-to-date study of conflict of laws & focuses on its three main areas: the law of obligations, law of property, & law of persons. It provides fresh perspectives on the subject & analyses its significance in the dynamic contemporary world. The work not only lucidly examines the inter-territorial conflicts but also lays a special emphasis on inter-personal disputes in the Indian context. It evaluates the role of various international instruments & conventions including The Hague Convention on private international law designed to resolve international conflicts.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 30, 2019).
Keywords: Conflict of laws -- India; Conflict of laws -- India -- Cases